A case of erosive-ulcerating bulbitis after long-term use of proton pump inhibitors in a smoking patient with chronic non-atrophic gastritis - Avramenko, A.; Magdenko, A.; Dubinets, T.; Vasyuk, V.; Makarova, G. (Journal of Education, Health and Sport, 2025)
A case of erosive and ulcerative bulbitis in a smoking patient with chronic non-atrophic gastritis was analyzed and a pathogenetic explanation was provided. It was discovered that the patient had previously been diagnosed with HP infection, for which he had undergone anti-Helicobacter therapy. For the past three months, the patient had regularly taken proton pump inhibitors (omeprazole) for heartburn, and over the past one month, his daily cigarette intake had increased (from one pack to two packs). Three different examinations (ELISA, urease test, and microscopy of stained gastritis smears) did not reveal HP infection. However, a breath test revealed a high increase (17 mm) in exhaled ammonia, the source of which was smoking and which caused the development of erosive and ulcerative bulbitis.